SYNTHESIS and CHARACTERIZATION OF CATALYSTS Ni-Cu SYSTEM SUPPORTED ON CLAY AND ALUMINA AND ITS APPLICATION IN HYDROGENATION OF OILS - Paredes, Luis (2001)
In the present work the catalytic behavior of the system Ni-Cu/supported on clay and alumina has been studied. The catalysts were prepared at a concentratlon of 1O% W of metalllc content. The method used in the preparation was impregnatlon, starting form the corresponding nitrates followed by a subsequent drying and calclnation. The elemental quantitative analysis was accomplished by Atomic Absorption. The presence of the phases NIO and CuO was confirmed by DRX. The activity of the catalysts were tested in a batch reactor at 455 ºK and 500 r.p.m. for 200 ml/min of hydrogen during 2 and 4 hours. The greater activity was observed in the catalyst with a theoretical molar fraction of 0.75 with respect to the nickel, in whlch is observed a decrease of the iodine index of the sunflower oil from 84.28 to 56.95 in a period of 4 hours.